2018
DOI: 10.1002/jor.23882
|View full text |Cite
|
Sign up to set email alerts
|

Mitoprotective therapy preserves chondrocyte viability and prevents cartilage degeneration in an ex vivo model of posttraumatic osteoarthritis

Abstract: This study is the first investigation of cardiolipin-targeted mitoprotective therapy in cartilage. These results suggest that even when treatment is delayed by up to 12 h after injury, mitoprotection may be a useful strategy in the prevention of PTOA. © 2018 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 9999:1-10, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 67 publications
(112 reference statements)
4
31
0
Order By: Relevance
“…In the context of diseases outside of the musculoskeletal umbrella, mitochondrial protection and re-stabilization has emerged as a tool to halt disease progression or restore organ functionality (Eirin et al, 2014; Szeto, 2008; Szeto and Schiller, 2011). While our group has recently reported on preliminary evidence of mitochondrial protection in cartilage (Delco et al, 2018) the data from the present study indicate that mitochondrial stabilization may pose a robust therapeutic target in cartilage disease or degeneration.…”
Section: Discussionmentioning
confidence: 48%
“…In the context of diseases outside of the musculoskeletal umbrella, mitochondrial protection and re-stabilization has emerged as a tool to halt disease progression or restore organ functionality (Eirin et al, 2014; Szeto, 2008; Szeto and Schiller, 2011). While our group has recently reported on preliminary evidence of mitochondrial protection in cartilage (Delco et al, 2018) the data from the present study indicate that mitochondrial stabilization may pose a robust therapeutic target in cartilage disease or degeneration.…”
Section: Discussionmentioning
confidence: 48%
“…The aim of this study was to understand the relationships between adenosine signaling via the A2AR and mitochondrial function, and dynamics in chondrocytes. Mitoprotective therapies such as antioxidants, caspase inhibitors, and Szeto‐Schiller mitoprotective peptides have had promising results in experimental OA models, but little is understood about their potential roles on the reversal of chronic inflammaging in vivo. Before this publication, no other group has been able to demonstrate the mitoprotective effects on chondrocytes of a compound that has already been shown to modulate OA progression by increasing cartilage volumes in animal models …”
Section: Discussionmentioning
confidence: 99%
“…Chen et al ( 2019 ) reported that scaffold-based delivery of EVs enhanced M2 polarization of synovial macrophages, reduced fibrocartilage formation, and effectively restored chondrocyte mitochondrial dysfunction, implying mitoprotective effects (Chen et al, 2019 ). Mitoprotection can be considered as specific antioxidative potential and has been found to prevent intracellular stress, apoptosis and catabolic processes after cartilage injury (Delco et al, 2018 ; Bartell et al, 2020 ).…”
Section: Therapeutic Application Of Msc-evs In Musculoskeletal Disordmentioning
confidence: 99%